Challenging Anatomies for TAVR—Bicuspid and Beyond - Saad, Mohammed; Seoudy, Hatim; Frank, Derk (Frontiers in Cardiovascular Medicine, 2021)
Transcatheter aortic valve replacement has emerged as the standard treatment for the majority of patients with symptomatic aortic stenosis. As transcatheter aortic valve replacement expands to patients across all risk groups, optimal patient selection strategies and device implantation techniques become increasingly important. A significant number of patients referred for transcatheter aortic valve replacement present with challenging anatomies and clinical indications that had been historically considered a contraindication for transcatheter aortic valve replacement. This article aims to highlight and discuss some of the potential obstacles that are encountered in clinical practice with a particular emphasis on bicuspid aortic valve disease.